Meanings of money in literature: D.J. Taylor’s novel Kept (2006) as a test case for exploring cognitive functions of literature - Nünning, Vera (The cultural life of money, 2015)
Das Kapitel Meanings of Money in Literature: D. J. Taylor’s Novel Kept (2006) as a Test Case for Exploring Cognitive Functions of Literature erschien in The Cultural Life of Money auf Seite 165.